Image of Soviet medicine as a historical memory component and health behavior factor in the modern youth - Valery V. Suvorov; Lyudmila V. Klimovich; Leonid A. Shaipak; Anton R. Kiselev (Russian Open Medical Journal)
Historical memory refers to the way people create specific accounts not only for political occasions and heroic moments of the past but also for healthcare system, doctors, and medical practices. The image of Soviet medicine has been perceived within two discourses: as a part of collective memory about the Soviet era and as a part of modern medicine perception. Most of the time, the image of Soviet medicine, the main feature of which was its being free-of-charge, is often contrasted with modern medical practices, many organisational features of which have caused dissatisfaction among citizens. However, modern approaches to treatment are accepted to be superior to the Soviet ones. Different interpretations of the image of the Soviet medicine influence citizens’ trust in the modern healthcare system by percolating public consciousness. Overcoming the contradiction in the perception of the Soviet and modern healthcare systems could have a positive impact not only on attitudes towards health, but also on the formation of the civic consciousness of modern citizens, especially of younger generations.